Technical Financial Innovation, Solving the Interoperability Problems of Europe The INFINTECH Legacy Part III - Serrano, Martín (NowOpen, 2023)
This third and final part of the INFINITECH book series begins by providing a definition for Fintech, namely: the use of technology to underpin the delivery of financial services. The book further discusses why Fintech is the focus of industry nowadays as the waves of digitization and the way financial technology (FinTech) and insurance technology (InsuranceTech) are rapidly transforming the financial and insurance services industry. The book also introduces technology assets that follow the Reference Architecture (RA) for BigData, IoT and AI applications. Moreover, the series of assets includes the domain area where applications from the INFINITECH innovation project and the concept of innovation for the financial sector are described. Further described is the INFINITECH Marketplace and its components including details of available assets, as well as a description of solutions developed in INFINITECH.